Efficient delivery of small RNAs to podocytes in vitro by direct exosome transfection - Tim Lange; Luzia Maron; Claudia Weber; Doreen Biedenweg; Rabea Schlüter; Nicole Endlich (Journal of Nanobiotechnology)
Abstract Background Podocytes are a crucial component of the glomerular filtration barrier, and changes in their 3D structure contribute to over 80% of chronic kidney disease (CKD) cases. Exosomal small RNAs play a key role in cell–cell communication in CKD and may serve as nanocarriers for delivering small RNAs into podocytes. However, the uptake of exosomal cargo by podocytes remains poorly understood. This study explores the use of isolated exosomes, directly transfected with fluorescently-labeled small RNAs, for tracking and delivering small RNAs to cultured podocytes. Methods Exosomes were isolated from immortalized murine podocytes and transfected with Cy3-labeled siRNA and miRNA controls using the ExoFect siRNA/miRNA Transfection Kit. We characterized the transfected exosomes via transmission electron microscopy (TEM) and Western blot for exosomal markers CD9 and TSG101. Subsequently, we co-cultured these exosomes with podocytes and used confocal laser-scanning microscopy (cLSM), and structured illumination microscopy (SIM) to visualize cargo uptake, confirmed through flow cytometry, imaging flow cytometry and immunofluorescence staining for Rab5, Rab7, and CD9. The isolated exosomes were also transfected with pre-miR-21 and filamin A (FlnA)-siRNAs before being co-cultured with podocytes. We confirmed the efficiency of transfection and knockdown using RT-qPCR, Western blotting, and immunofluorescence staining. Results TEM revealed that the exosomes maintained a consistent shape and size of approximately 20 nm posttransfection and exhibited a stable expression of CD9 and TSG101. Flow cytometry and immunofluorescence imaging showed that podocytes take up Cy3-labeled exosomal miRNAs and siRNAs time-dependently, utilizing various mechanisms, including encapsulation within vesicular structures, endocytosis and free distribution within the cells. Transfection of exosomes with FlnA-siRNAs resulted in a significant 2.8-fold reduction of filamin A expression in co-cultured podocytes, while pre-miR-21-transfected exosomes led to a remarkable 338-fold increase in mature miR-21 levels. Conclusions These findings demonstrate that direct exosome transfection with fluorescently-labeled small RNAs is an effective method for tracking exosomal cargo in podocytes. This study is the first to show that directly transfected exosomes can deliver small RNAs to podocytes in vitro, suggesting their potential as RNA carriers for therapeutic strategies in more complex settings. Graphical Abstract